2003
DOI: 10.1007/s11882-003-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental autoimmune encephalomyelitis: Cytokines, effector t cells, and antigen-presenting cells in a prototypical th1-mediated autoimmune disease

Abstract: Experimental autoimmune encephalomyelitis (EAE) is widely depicted as the prototypical CD4+ Th1-mediated autoimmune disease. Microglia and perivascular macrophages are believed to act as antigen-presenting cells during the effector phase of EAE. In this article, recent data that challenge these conceptions are reviewed. Several recent studies have shown that myelin-reactive CD8+ T cells can mediate inflammatory demyelination. Furthermore, dendritic-like cells have been detected in EAE lesions and implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 73 publications
(61 reference statements)
0
38
0
Order By: Relevance
“…We observed increased amounts of TNF-␣ , IL-12 and IFN-␥ in the CNS of control animals treated with IFA+PBS only. This is probably due to an adjuvant-induced increase in the blood-brain barrier permeability, as also shown by others [50] , and it might explain why EAE has been considered a prototypic T H 1-mediated disease [41,51] .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We observed increased amounts of TNF-␣ , IL-12 and IFN-␥ in the CNS of control animals treated with IFA+PBS only. This is probably due to an adjuvant-induced increase in the blood-brain barrier permeability, as also shown by others [50] , and it might explain why EAE has been considered a prototypic T H 1-mediated disease [41,51] .…”
Section: Discussionmentioning
confidence: 54%
“…3 ), which challenges the theory that the T H 1 response is detrimental in MS/EAE. The essential aspect concerning cytokines seems to be timing in relation to disease state [41,42] . Thus, TNF-␣ and IFN-␥ might be detrimental in inducing resident CNS cell death during the initial stages of the disease, but later these cytokines may play a beneficial role in inducing remyelination and immune cell death, as shown in other studies [37,[43][44][45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the EAE model in this work exhibited a T cell-mediated immune response in favor to Th1 pattern over Th2 pattern reflected as an imbalance in their associated cytokines where the pro-inflammatory TNF-α was significantly increased without change in the anti-inflammatory IL-10. Previous studies reported that Th2-related cytokines including IL-10 have been associated with inflammation reduction and improvement of symptoms in MS patients, while Th1 cytokines such as TNF-α have been shown to increase inflammation with subsequent disease progression and worsening of symptoms (Sharief and Hentges, 1991;Segal, 2003;Miller et al, 2004;Imitola et al, 2005). TNF-α mediates inflammatory reaction by altering the blood brain barrier, influences lymphocyte behavior, and induces tissue damage with astrogliosis and destruction of oligodendrocytes (Issazadeh et al, 1995;Montgomery and Bowers, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The demyelination of the CNS was concerned with the overactivity of effector T cells, infiltration of inflammatory cells in the CNS, increased production of proinflammatory cytokines, and inflammatory molecules. 5,6 Cytokines such as…”
Section: Introductionmentioning
confidence: 99%